Regulator Perspective on Halal Air Cargo Warehouse Compliance - Muhamad Munzir Khairuddin; Nor Aida Abdul Rahman; Mohammad Fakhrulnizam Mohammad; Zawiah Abdul Majid; Md Fauzi Ahmad (International Journal of Supply Chain Management, 2018)
In establishing a successful Halal supply chain, Syariah compliancy has emerged as a key issue. Halal transport and Halal warehouse play a significant role in maintaining the integrity of the Halal products from point of origin to end of consumption. The escalating demand for halal food has encouraged warehouse operators to devise a new business plan to cater to the present business trend. Warehousing or storage is a critical factor where cross-contamination may occur. As such, this study explored the Halal warehouse compliance from the perspective of regulators. This study adopted the qualitative approach by carrying out interview sessions, document review, and observation as the primary methods for data collection. The outcomes pointed out eight main factors that ascertain Halal warehouse compliance from the perspective of regulator, which are: management member, comprehensive training, Halal standard adoption, supplier, standard operating procedure (SOP), internal halal committee, documentation, and knowledge. This study appears to be a pioneer that probes into Halal warehouse compliance in Malaysia.